Training in interprofessional learning and collaboration: An evaluation of the interprofessional education program in the scale-up phase in Antwerp (Belgium) - Tsakitzidis Giannoula; Olmen Josefien Van; Royen Paul Van (Sciendo, 2021)
Curricula are reviewed and adapted in response to a perceived need to improve interprofessional collaboration for the benefit of patient care. In 2005, the module Interprofessional Collaboration in Healthcare (IPCIHC) was developed by the Antwerp University Association (AUHA). The program was based upon a concept of five steps to IPCIHC. This educational module aims to help graduates obtain the competence of interprofessional collaborators in health care.